Primary appendicular soft‐tissue sarcoma resection: What tumour parameters affect wound closure planning?. Issue 6 (13th October 2019) - Cawley, Derek T.; Barrett, Peter; Moran, Barry; McGoldrick, Niall P.; Gillham, Charles; Codd, Mary; O'Toole, Gary C.; Kieser, David C.
Abstract: Wound closure after wide, local excision of an appendicular soft‐tissue sarcoma (STS) can be challenging. This study evaluates the value of magnetic resonance imaging (MRI)‐based tumour parameters in planning wound closure. A total of 71 patients with a primary limb‐based STS, excluding vascular or osseous involvement, excluding the shoulder or hand and hip or foot were included. Axial MRI images were used to measure the circumferences and cross‐sectional areas of the limb, bone, and tumour. The tumour diameter, length, and depth at the level of maximal tumour dimension were measured to identify the tumour's relative contribution to the planning of optimal wound closure management through primary closure (PC) or reconstructive surgery (RS). Eighteen patients required planned wound RS. Wound complications occurred in 14% overall. Tumours, which were closed by PC, were of significantly greater depth, shorter radial diameter, and shorter tumour circumference relative to those closed by RS. On multivariate analysis, tumour depth was the greatest contributory factor in predicting type of wound closure. A quantitative analysis of MRI‐based tumour parameters demonstrates tumour depth as the most predictive factor in planning for the type of wound closure and may prove beneficial in providing greater insight into planned wound management of sarcoma resection.